Studi Perbandingan Efek Anestesi Eter dan Kloroform pada Tikus Wistar (Rattus norvegicus) : Analisis Waktu Induksi dan Durasi Anestesi - Haryanto Haryanto; Zulkifli Zulkifli; Firly Ananda Pertiwi; Syabila Putri Amalia; Nurpinanda Nurpinanda; Ulfa Adelia Dwi Putri (Pusat Riset dan Inovasi Nasional, 2025)
Anesthesia is a procedure that eliminates pain centrally with reversible unconsciousness. The purpose of this study was to compare the effects of ether and chloroform anesthesia on Wistar rats, with a particular focus on the induction time and duration of anesthesia associated with both anesthetic agents. Twelve male Wistar rats were divided into two treatment groups: the ether group and the chloroform group. The results showed that chloroform had a faster onset compared to ether, approximately 6.84 minutes faster, and a longer duration, approximately 22.41 minutes longer. The fastest onset was observed with chloroform, while the shortest duration was observed with ether. Based on these findings, these results can serve as a reference for the duration of anesthesia in experimental animals when using ether and chloroform.